Subchannel Analysis of Wire Wrapped SCWR Assembly. (23rd February 2014) - Shan, Jianqiang; Wang, Henan; Liu, Wei; Song, Linxing; Chen, Xuanxiang; Jiang, Yang
Abstract : Application of wire wrap spacers in SCWR can reduce pressure drop and obtain better mixing capability. As a consequence, the required coolant pumping power is decreased and the coolant temperature profile inside the fuel bundle is flattened which will obviously decrease the peak cladding temperature. The distributed resistance model for wire wrap was developed and implemented in ATHAS subchannel analysis code. The HPLWR wire wrapped assembly was analyzed. The results show that: (1) the assembly with wire wrap can obtain a more uniform coolant temperature profile than the grid spaced assembly, which will result in a lower peak cladding temperature; (2) the pressure drop in a wire wrapped assembly is less than that in a grid spaced assembly, which can reduce the operating power of pump effectively; (3) the wire wrap pitch has significant effect on the flow in the assembly. SmallerH w i r e / D r o d will result in stronger cross flow a more uniform coolant temperature profile, and also a higher pressure drop.